Fiber reinforced composite material, preparation method and application thereof, and road traffic signboard

By using fiber-reinforced composite materials, including stacked basalt fiber cloth and resin matrix, the problem of aluminum alloy signs is solved for corrosion in complex environments, and high-strength, corrosion-resistant and long-life traffic signs are achieved.

CN119823532AActive Publication Date: 2025-04-15JILIN TRAFFIC SCI ACAD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510052761.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-14
Publication Date
2025-04-15
Estimated Expiration
2045-01-14

AI Technical Summary

Technical Problem

The existing road traffic sign material aluminum alloy is prone to corrosion and has poor aging resistance in complex outdoor environments, resulting in a short service life and affecting highway safety.

Method used

Using fiber-reinforced composite materials, including laminated basalt fiber cloth and resin matrix, the mechanical properties and corrosion resistance of the material are improved through specific laying sequences and modified metal oxide additions.

Benefits of technology

The fiber-reinforced composite material has been achieved with light weight, high strength and good aging resistance, extending the service life of traffic signs and reducing production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005240452630000121
    Figure BDA0005240452630000121
  • Figure HDA0005240452640000011
    Figure HDA0005240452640000011
  • Figure HDA0005240452640000012
    Figure HDA0005240452640000012
Patent Text Reader

Abstract

The invention belongs to the technical field of sign board materials, and particularly relates to a fiber reinforced composite material, a preparation method and application thereof and a road traffic sign board. The fiber reinforced composite material provided by the invention comprises a matrix and a reinforcement body embedded in the matrix, the reinforcement body is laminated basalt fiber cloth; the basalt fiber cloth on the upper surface and the lower surface of the reinforcement body is plain cloth formed by weaving basalt fibers; the included angle between the basalt fibers in any two adjacent layers of basalt fiber cloth is 0-90 degrees; and the matrix is resin. According to the composite material provided by the invention, under the combined action of the basalt fiber and the resin, the mechanical property, the ultraviolet aging resistance and the salt spray corrosion resistance of the fiber reinforced composite material are improved, and the traffic sign board prepared from the fiber reinforced composite material has longer service life.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of sign board materials, and specifically relates to a fiber reinforced composite material and a preparation method and application thereof, and a road traffic sign board. Background Art

[0002] Road traffic signs are a type of safety facility that uses graphic symbols and text to convey specific information for managing road traffic. They are generally installed on the side of the road or above the road (gantry type).

[0003] Most of the existing road traffic signs are made of aluminum alloy materials, generally using 3003 aluminum alloy plates; large signs (15m 2 The above) or signs used in coastal and windy areas generally use aluminum alloy plates with grades of 3004 or 3104. Although aluminum alloy materials are relatively light and high in strength, they are easily polluted, corroded and destroyed after experiencing long-term wind and rain, temperature changes, ultraviolet radiation, salt spray erosion and other effects in complex outdoor environments. They have poor aging resistance and short service life, which seriously affects highway driving safety.

[0004] Therefore, developing a new material with strong durability to replace aluminum alloy materials for the preparation of road traffic signs is of great significance to maintaining the long-term stable and high-quality operation of highway facilities. Summary of the invention

[0005] In view of this, the present invention provides a fiber reinforced composite material, a preparation method and application thereof, and a road traffic sign. The fiber reinforced composite material provided by the present invention has light weight, high strength and good aging resistance, and the traffic sign prepared using the fiber reinforced composite material has a long service life.

[0006] In order to solve the above technical problems, the present invention provides a fiber reinforced composite material, comprising a matrix and a reinforcement embedded in the matrix;

[0007] The reinforcement is a stacked basalt fiber cloth; the basalt fiber cloth on the upper and lower surfaces of the reinforcement is a plain cloth woven from basalt fibers; the angle between the basalt fibers in any two adjacent layers of basalt fiber cloth is 0 to 90°;

[0008] The matrix is ​​resin.

[0009] Preferably, the basalt fiber cloth in the reinforcement except the upper and lower surfaces includes one or more of plain cloth, unidirectional cloth and multi-axial cloth woven from basalt fibers.

[0010] Preferably, the resin comprises epoxy resin, vinyl resin or unsaturated resin;

[0011] The resin also includes a modified metal oxide; the modified metal oxide is a metal oxide with a coupling agent grafted on the surface;

[0012] The mass ratio of the modified metal oxide to the resin in the matrix is ​​0.3 to 6:100.

[0013] Preferably, the modified metal oxide includes one or more of modified cerium oxide, modified zinc oxide and modified titanium oxide.

[0014] Preferably, the preparation method of the modified cerium oxide comprises the following steps:

[0015] dissolving a first coupling agent in a first ethanol aqueous solution to obtain a coupling agent solution;

[0016] first dispersing nano cerium oxide particles in water to obtain a cerium oxide dispersion;

[0017] The coupling agent solution and the cerium oxide dispersion are first mixed, the pH value is adjusted to 7 to 11, and then a first grafting modification is performed to obtain the modified cerium oxide;

[0018] The preparation method of the modified zinc oxide comprises the following steps:

[0019] dispersing the nano zinc oxide particles in a second ethanol aqueous solution to obtain a zinc oxide dispersion;

[0020] The zinc oxide dispersion and the second coupling agent are mixed for a second time to perform a second grafting modification to obtain the modified zinc oxide;

[0021] The preparation method of the modified titanium oxide comprises the following steps:

[0022] dispersing the nano titanium oxide particles in water to obtain a titanium oxide dispersion;

[0023] The titanium oxide dispersion, the third coupling agent and ethanol are mixed for a third time, the pH value is adjusted to 5-7, and then a third grafting modification is performed to obtain the modified titanium oxide.

[0024] The present invention also provides a method for preparing the fiber-reinforced composite material described in the above technical solution, comprising the following steps:

[0025] mixing the resin and the curing agent to obtain a composite resin;

[0026] The basalt fiber cloths are stacked to obtain a reinforcement body; the basalt fiber cloths on the upper and lower surfaces of the reinforcement body are both plain cloths woven from basalt fibers; the angle between the basalt fibers in any two adjacent layers of basalt fiber cloth is 0 to 90 degrees;

[0027] The composite resin and the reinforcement are mixed and molded to obtain the fiber-reinforced composite material.

[0028] Preferably, the mass ratio of the curing agent to the resin is 60 to 100:100;

[0029] The mixing process also adds a modified metal oxide;

[0030] The molding method includes vacuum infusion molding;

[0031] The vacuum infusion molding process has a temperature of 150-200° C., a pressure of 3-5 MPa, and a time of 80-120 min.

[0032] The present invention also provides the use of the fiber-reinforced composite material described in the above technical solution or the fiber-reinforced composite material prepared by the preparation method described in the above technical solution in the preparation of road traffic signs.

[0033] The present invention also provides a road traffic sign, comprising a base plate, a slide groove arranged on either side of the base plate, and a reflective film arranged on the other side of the base plate;

[0034] The base plate is the fiber-reinforced composite material described in the above technical solution or a fiber-reinforced composite material prepared by the preparation method described in the above technical solution.

[0035] Preferably, the slide groove is made of aluminum alloy;

[0036] The connection method between the slideway and the bottom plate includes riveting or glue riveting; the adhesive for glue riveting includes epoxy resin, vinyl resin or unsaturated resin.

[0037] The present invention provides a fiber-reinforced composite material, including a matrix and a reinforcement embedded in the matrix; the reinforcement is a stacked basalt fiber cloth; the basalt fiber cloth on the upper and lower surfaces of the reinforcement is a plain cloth woven from basalt fibers; the angle between the basalt fibers in any two adjacent layers of basalt fiber cloth is 0-90°; the matrix is ​​resin. The present invention forms a reinforcement by plying basalt fiber cloth in a certain order, which can significantly improve the mechanical properties of the composite material while ensuring the light weight of the composite material; the present invention uses resin as a matrix material, which can ensure that the composite material has good corrosion resistance; the composite material provided by the present invention improves the mechanical properties, anti-ultraviolet aging performance and salt spray erosion resistance of the fiber-reinforced composite material under the joint action of basalt fiber and resin, and the traffic sign prepared by using the composite material has a longer service life. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 This is a rear view of the road traffic sign prepared by the present invention;

[0039] Figure 2A side view of a road traffic sign prepared by the present invention;

[0040] Figure 3 This is an AA cross-sectional view of the road traffic sign prepared by the present invention;

[0041] In the figure, 1 is the bottom plate, 2 is the aluminum alloy slide, 3 is the reflective film, and 4 is the rivet. DETAILED DESCRIPTION

[0042] The invention provides a fiber reinforced composite material, comprising a matrix and a reinforcement embedded in the matrix.

[0043] In the present invention, the matrix is ​​a resin; the resin may include epoxy resin, vinyl resin or unsaturated resin. As a specific embodiment of the present invention, the resin may also include a modified metal oxide; the modified metal oxide is a metal oxide with a coupling agent grafted on the surface; the mass ratio of the modified metal oxide to the resin in the matrix may be 0.3 to 6:100, and may be specifically 0.5:100, 1:100, 2:100, 3:100, 4:100, 5:100 or 6:100.

[0044] As a specific embodiment of the present invention, the modified metal oxide may include one or more of modified cerium oxide, modified zinc oxide and modified titanium oxide, and may specifically be modified cerium oxide, a mixture of modified zinc oxide and modified titanium oxide, a mixture of modified cerium oxide and modified zinc oxide, a mixture of modified cerium oxide and modified titanium oxide, a mixture of modified zinc oxide and modified titanium oxide, modified cerium oxide, modified zinc oxide or modified titanium oxide. As a specific embodiment of the present invention, when the modified metal oxide is a mixture of modified cerium oxide, modified zinc oxide and modified titanium oxide, the mass ratio of the modified cerium oxide, modified zinc oxide and modified titanium oxide can be 1.0-2.5:0.5-1.5:1.0, and can be specifically 2.5:1.5:1.0; when the modified metal oxide is a mixture of modified cerium oxide and modified zinc oxide, the mass ratio of the modified cerium oxide and modified zinc oxide can be 1.5-3.0:1; when the modified metal oxide is a mixture of modified cerium oxide and modified titanium oxide, the mass ratio of the modified cerium oxide and modified titanium oxide can be 1.0-2.0:1; when the modified metal oxide is a mixture of modified zinc oxide and modified titanium oxide, the mass ratio of the modified zinc oxide and modified titanium oxide can be 0.5-1.5:1. As a specific embodiment of the present invention, when the modified metal oxide is modified cerium oxide, the mass ratio of the modified cerium oxide to the resin can be 3 to 5:100; when the modified metal oxide is modified zinc oxide, the mass ratio of the modified zinc oxide to the resin can be 0.5 to 3:100; when the modified metal oxide is modified titanium oxide, the mass ratio of the modified titanium oxide to the resin can be 1 to 5:100.

[0045] As a specific embodiment of the present invention, the method for preparing the modified cerium oxide may include the following steps:

[0046] dissolving a first coupling agent in a first ethanol aqueous solution to obtain a coupling agent solution;

[0047] first dispersing nano cerium oxide particles in water to obtain a cerium oxide dispersion;

[0048] The coupling agent solution and the cerium oxide dispersion are first mixed, the pH value is adjusted to 7-11, and then a first grafting modification is performed to obtain the modified cerium oxide.

[0049] As a specific embodiment of the present invention, the first coupling agent can be a silane coupling agent, specifically a KH550 coupling agent, a KH560 coupling agent or a KH570 coupling agent; the volume fraction of ethanol in the first ethanol aqueous solution can be 70-80%, or 70-75%; the volume ratio of the first coupling agent to the first ethanol aqueous solution can be 4-6:100, or 5-6:100. As a specific embodiment of the present invention, the first dissolution can be carried out under stirring, and the stirring time can be 20-30 minutes; the present invention has no special requirements for the stirring speed, as long as the dissolution is complete.

[0050] As a specific embodiment of the present invention, the average particle size of the nano cerium oxide particles can be 30-100 nm, or 50-80 nm; the water can be deionized water; the mass ratio of the nano cerium oxide particles to water can be 10-15:100, or 12-14:100. As a specific embodiment of the present invention, the first dispersion can be carried out under stirring, and the stirring time can be 40-60 minutes; the present invention has no special requirements on the stirring speed, as long as it can be dispersed evenly.

[0051] The present invention has no special limitation on the first mixing, as long as it can be mixed evenly. As a specific embodiment of the present invention, the pH value of the system after the first mixing is 7-11, and can also be 8-10; the present invention has no special requirements for the method of adjusting the pH value, and the conventional method in the field can be adopted. As a specific embodiment of the present invention, the temperature of the first grafting modification can be 65-75°C, and can also be 68-70°C; the time of the first grafting modification can be 6-8h; the present invention can be accompanied by stirring during the first grafting modification process, and the present invention has no special requirements for the stirring, as long as it can fully react.

[0052] As a specific embodiment of the present invention, the first grafting modification may further include: performing solid-liquid separation on the system after the first grafting modification, washing the solid obtained by the solid-liquid separation with water and then freeze-drying to obtain the modified cerium oxide. As a specific embodiment of the present invention, the solid-liquid separation may be centrifugal; the freeze-drying temperature may be -80 to -40°C, or -60 to -50°C; the freeze-drying time may be more than 24 hours, or 24 to 30 hours.

[0053] As a specific embodiment of the present invention, the preparation method of the modified zinc oxide may include the following steps:

[0054] dispersing the nano zinc oxide particles in a second ethanol aqueous solution to obtain a zinc oxide dispersion;

[0055] The zinc oxide dispersion and the second coupling agent are mixed for a second time to perform a second grafting modification to obtain the modified zinc oxide.

[0056] As a specific embodiment of the present invention, the average particle size of the nano zinc oxide particles can be 30-100nm, or 50-80nm; the volume fraction of ethanol in the second ethanol aqueous solution can be 70-80%, or 70-75%; the mass of the nano zinc oxide particles and the volume ratio of the second ethanol aqueous solution can be 5-8mg:1mL, or 6-7mg:1mL. As a specific embodiment of the present invention, the second dispersion can be carried out under ultrasonic conditions, and the ultrasonic time can be 20-30min; the present invention has no special requirements on the power of the ultrasound, as long as it can be dispersed evenly.

[0057] As a specific embodiment of the present invention, the second coupling agent can be a silane coupling agent or a titanate coupling agent, and can be specifically a KH550 coupling agent, a KH560 coupling agent or a KH570 coupling agent; the volume ratio of the second coupling agent to the second ethanol aqueous solution can be 3 to 5:100, or can be 4 to 5:100.

[0058] The present invention has no special requirements for the second mixing, as long as the mixing can be uniform.

[0059] As a specific embodiment of the present invention, the temperature of the second grafting modification can be 50-80°C, or 60-70°C; the time of the second grafting modification can be 6-8h; the second grafting modification process of the present invention can be accompanied by stirring and reflux, and the present invention has no special requirements for the stirring, as long as it can fully react.

[0060] As a specific embodiment of the present invention, the second graft modification may further include: performing solid-liquid separation on the second graft modification system, washing the solid obtained by the solid-liquid separation with water and then vacuum drying to obtain the modified zinc oxide. As a specific embodiment of the present invention, the solid-liquid separation may be centrifugal; the water used for washing may be deionized water; the temperature of the vacuum drying may be 35 to 45°C, or 35 to 40°C; the time of the vacuum drying may be more than 8 to 12 hours, or 9 to 10 hours.

[0061] As a specific embodiment of the present invention, the preparation method of the modified titanium oxide may include the following steps:

[0062] dispersing the nano titanium oxide particles in water to obtain a titanium oxide dispersion;

[0063] The titanium oxide dispersion, the third coupling agent and ethanol are mixed for a third time, the pH value is adjusted to 5-7, and then a third grafting modification is performed to obtain the modified titanium oxide.

[0064] As a specific embodiment of the present invention, the average particle size of the nano titanium oxide particles can be 30-100 nm, or 50-80 nm; the water can be deionized water; the mass ratio of the nano titanium oxide particles to water can be 3-5:100, or 4-5:100. As a specific embodiment of the present invention, the third dispersion can be carried out under stirring, and the stirring time can be 20-30 minutes; the present invention has no special requirements on the stirring speed, as long as it can be dispersed evenly.

[0065] As a specific embodiment of the present invention, the third coupling agent can be a silane coupling agent or a titanate coupling agent, and can be specifically a KH550 coupling agent, a KH560 coupling agent or a KH570 coupling agent; the ethanol can be anhydrous ethanol; the mass ratio of the nano-titanium oxide particles to the third coupling agent can be 1-2:1; the volume ratio of the ethanol to water can be 1:2.

[0066] The present invention has no special requirements for the third mixing, as long as it can be mixed evenly; the present invention has no special requirements for the method of adjusting the pH value of the system after the third mixing, and the conventional method in the art can be used.

[0067] As a specific embodiment of the present invention, the temperature of the third graft modification can be 40-60°C, or 45-50°C; the time of the third graft modification can be 1-2h; the present invention can be accompanied by stirring during the third graft modification process, and the present invention has no special requirements for the stirring, as long as it can fully react.

[0068] As a specific embodiment of the present invention, the third graft modification may further include: performing solid-liquid separation on the system after the third graft modification, and drying the solid obtained by the solid-liquid separation to obtain the modified titanium oxide. As a specific embodiment of the present invention, the solid-liquid separation may be filtering; the drying may be drying, and the drying temperature may be 100-120°C, or 100-110°C; the present invention has no special requirements for the drying time, as long as the surface solvent can be removed.

[0069] The modified metal oxide added to the resin of the present invention has the function of absorbing ultraviolet rays, can further improve the ultraviolet aging resistance of the composite material, and has the effect of strengthening and toughening the resin.

[0070] In the present invention, the reinforcement is a stacked basalt fiber cloth; the basalt fiber cloth on the upper and lower surfaces of the reinforcement is a plain cloth woven from basalt fibers; the angle between the basalt fibers in any two adjacent layers of basalt fiber cloth is 0 to 90°, specifically 0°, 45° or 90°. As a specific embodiment of the present invention, the basalt fiber cloth in the reinforcement except the upper and lower surfaces may include one or more of a plain cloth, a unidirectional cloth and a multi-axial cloth woven from basalt fibers. In the present invention, when the basalt fiber cloth in the reinforcement except the upper and lower surfaces is a plain cloth, a multi-axial cloth and a unidirectional cloth, the plain cloth is arranged in the outer layer of the composite material, the unidirectional cloth is arranged in the middle of the composite material, and the multi-axial cloth is arranged between the plain cloth layer and the unidirectional cloth layer. The present invention has no special requirements for the number of layers of basalt fiber cloth in the reinforcement, and it can be designed according to the thickness of the fiber-reinforced composite material.

[0071] The present invention also provides a method for preparing the fiber-reinforced composite material described in the above technical solution, comprising the following steps:

[0072] mixing the resin and the curing agent to obtain a composite resin;

[0073] The basalt fiber cloths are stacked to obtain a reinforcement body; the basalt fiber cloths on the upper and lower surfaces of the reinforcement body are both plain cloths woven from basalt fibers; the angle between the basalt fibers in any two adjacent layers of basalt fiber cloth is 0 to 90 degrees;

[0074] The composite resin and the reinforcement are mixed and molded to obtain the fiber-reinforced composite material.

[0075] As a specific implementation of the present invention, the mass ratio of the curing agent to the resin can be 60 to 100:100, or 70 to 90:100.

[0076] As a specific embodiment of the present invention, modified metal oxides may be added during the mixing process; the total mass of the resin and the curing agent and the mass ratio of the modified metal oxide may be 100:0.3-6, and may be specifically 100:0.5, 100:1, 100:2, 100:3, 100:4, 100:5 or 100:6. The present invention has no particular limitation on the mixing method, as long as the mixing can be uniform.

[0077] As a specific embodiment of the present invention, the molding process may further include the following steps: in the process of laying basalt fibers, the composite resin is coated on the surface of each layer of basalt fiber cloth, and then pre-molding is performed. As a specific embodiment of the present invention, the mass of the composite resin coated on the unit surface of each layer of basalt fiber cloth can be 120-180 g / m 2 , can also be 140 ~ 160g / m2 As a specific embodiment of the present invention, the preforming method can be compression molding; the compression molding temperature can be 80-100°C, or 85-95°C; the compression molding pressure can be 0.8-1.2MPa, or 1MPa; the compression molding heat preservation and pressure holding time can be 55-65min, or 60min.

[0078] As a specific embodiment of the present invention, the molding method may include vacuum infusion molding; the temperature of the vacuum infusion molding may be 150-200°C, or 160-180°C; the pressure of the vacuum infusion molding may be 3-5MPa, or 3-4MPa; the heat preservation and pressure holding time of the vacuum infusion molding may be 80-120min, or 90-110min.

[0079] As a specific embodiment of the present invention, the molding process may further include: performing trimming after demoulding to obtain the fiber reinforced composite material. The present invention has no special requirements for the demoulding and trimming processes, and conventional methods in the art may be used.

[0080] The present invention also provides the use of the fiber-reinforced composite material described in the above technical solution or the fiber-reinforced composite material prepared by the preparation method described in the above technical solution in the preparation of road traffic signs.

[0081] The present invention also provides a road traffic sign, comprising a base plate, a slide groove arranged on either side of the base plate, and a reflective film arranged on the other side of the base plate;

[0082] The base plate is the fiber-reinforced composite material described in the above technical solution or a fiber-reinforced composite material prepared by the preparation method described in the above technical solution.

[0083] As a specific embodiment of the present invention, the material of the slide can be aluminum alloy material, and the grade of the aluminum alloy material can be 3004 or 3104; the present invention processes the shape of the slide into a circle, triangle, rectangle or regular hexagon according to actual needs. As a specific embodiment of the present invention, the connection method between the slide and the base plate includes riveting or glue riveting; the adhesive for glue riveting includes epoxy resin, vinyl resin or unsaturated resin, which can be consistent with the resin used for the matrix in the fiber reinforced composite material. The present invention adopts the riveting or glue riveting connection method to ensure that the sign board surface is flat and has a high connection strength.

[0084] As a specific implementation of the present invention, the reflective film can be pasted on the other side of the base plate.

[0085] Figure 1This is a rear view of the road traffic sign prepared by the present invention. Figure 2 For its side view, Figure 3 This is its AA cross-sectional view, where 1 is the bottom plate, 2 is the aluminum alloy slide, 3 is the reflective film, and 4 is the rivet.

[0086] The traffic sign prepared by the present invention has the following advantages:

[0087] 1. The present invention uses basalt fiber reinforced resin composite material as the sign base plate, connects the slideway and the sign base plate by a mixed connection method of glue and rivet, and then installs it on the column. The performance of the sign plate with basalt fiber reinforced resin composite material layer as the sign base plate meets the requirements of relevant national standards. Compared with aluminum alloy traffic sign plates, it has higher mechanical properties, anti-ultraviolet aging performance and salt spray erosion resistance, and longer service life.

[0088] 2. The present invention effectively reduces the number of processes, improves production efficiency, and correspondingly further reduces the cost while ensuring long-term reliable connection (bonding) between the structural parts and the reflective film and the base plate. The cost of the sign board using basalt fiber reinforced resin composite material as the sign base plate is more than 30% lower than that of the aluminum alloy sign board.

[0089] 3. The present invention uses basalt fiber reinforced resin composite material as the base plate to make traffic sign plates, which can reduce the use of aluminum and reduce the consumption of raw materials and energy in the production process of aluminum. At the same time, basalt fiber, as a green and environmentally friendly material, greatly reduces the carbon emissions in the production process.

[0090] In order to further illustrate the present invention, the technical solutions provided by the present invention are described in detail below in conjunction with embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0091] In the embodiment, the angle of basalt fiber cloth laying is defined as follows: the orientation direction of each layer of fiber cloth is determined by the direction of the fiber cloth product, the initial laying direction (i.e., the system coordinate axis direction) is defined as 0°, and the positive and negative direction angles are used to define the fiber cloth laying direction, and the direction angle range is 0° to 90°. The fiber cloth between 0° and 90° is represented by the angle between the fiber cloth orientation direction and 0° plus "+" or "-". If the fiber cloth is arranged in the positive quadrant of the coordinate axis, it is represented by "+", and if the fiber cloth is arranged in the negative quadrant of the coordinate axis, it is represented by "-". Arrange in the order of laying from top to bottom, and separate the layers with " / ".

[0092] Example 1

[0093] The modified metal oxides were prepared as follows:

[0094] The modified CeO2 nanoparticles were prepared as follows:

[0095] Dissolving the silane coupling agent KH550 in an ethanol aqueous solution with a volume fraction of 75% under stirring (25 min) to obtain a silane coupling agent aqueous solution A; wherein the volume ratio of the coupling agent KH550 to the ethanol aqueous solution is 5:100;

[0096] Add nano CeO2 particles with an average particle size of 60 nm to deionized water of the same volume as the silane coupling agent KH550, and stir for 50 minutes to obtain a cerium oxide dispersion; wherein the mass ratio of the nano CeO2 particles to water is 13:100;

[0097] The cerium oxide dispersion was poured into the silane coupling agent aqueous solution A, and the pH value was adjusted to 10 with glacial acetic acid. The first grafting modification was carried out by stirring at 70°C for 7 hours, and then centrifuged. The solid obtained by centrifugation was washed 3 times with deionized water and freeze-dried at -80°C for 24 hours to obtain modified nano-CeO2 particles.

[0098] The modified ZnO nanoparticles were prepared as follows:

[0099] The ZnO nanoparticles with an average particle size of 50 nm were subjected to ultrasonic dispersion treatment in a 75% volume fraction ethanol aqueous solution for 25 minutes to obtain a zinc oxide dispersion; wherein the mass ratio of the ZnO nanoparticles to the volume of the ethanol aqueous solution was 7 mg:1 mL;

[0100] The silane coupling agent KH550 was poured into the zinc oxide dispersion, stirred and refluxed at 60° C. for a second grafting modification for 7 hours, and then centrifuged; the solid obtained by centrifugation was washed with deionized water, and vacuum dried at 40° C. for 10 hours to obtain modified ZnO nanoparticles; wherein the volume ratio of the silane coupling agent KH550 to the ethanol aqueous solution was 4:100.

[0101] The modified TiO2 nanoparticles were prepared as follows:

[0102] TiO2 nanoparticles with an average particle size of 70 nm were stirred in deionized water for 25 minutes, and then silane coupling agent KH550 and anhydrous ethanol were added, the pH value of the system was adjusted to 6 with citric acid, and the third grafting modification was carried out by stirring at 50°C for 2 hours; the system after the third grafting modification was filtered, and the filtered solid was dried at 100°C and ground to obtain modified TiO2 nanoparticles; wherein the mass ratio of TiO2 nanoparticles to deionized water was 4:100, the mass ratio of TiO2 nanoparticles to silane coupling agent KH550 was 2:1, and the volume ratio of anhydrous ethanol to deionized water was 1:2.

[0103] The epoxy resin and the curing agent (5313A / B) are mixed in a mass ratio of 1:1 and stirred evenly, and then mixed with modified CeO2 nanoparticles, modified ZnO nanoparticles and modified TiO2 nanoparticles in a mass ratio of 2.5:1.5:1.0 to obtain a composite epoxy resin; wherein the total mass ratio of the modified CeO2 nanoparticles, the modified ZnO nanoparticles and the modified TiO2 nanoparticles to the total mass ratio of the epoxy resin and the curing agent is 5:100;

[0104] A mold matching the size of the reinforcement is used and a release agent is applied. The basalt fiber cloth is cut and laid in layers. The order of laying from top to bottom is: plain cloth 0° / plain cloth -45° / plain cloth 0° / plain cloth +45° / plain cloth 0°;

[0105] During the basalt fiber laying process, the composite epoxy resin is coated on the surface of each layer of basalt fiber cloth, and the mass of the resin coated on the unit surface of each layer of basalt fiber cloth is 150g / m 2 , and then perform preforming treatment, wherein the preforming method is compression molding, the compression molding temperature is 80°C, the pressure is 1.0Mpa, and the heat preservation and pressure holding time is 60min;

[0106] After the preforming process is completed, the stacked basalt fiber cloth and composite resin are molded and cured by vacuum infusion molding process, and then demolded and trimmed to obtain a fiber-reinforced composite material; the molding temperature is 170°C, the pressure is 4MPa, and the insulation and pressure holding time is 100min.

[0107] Example 2

[0108] A fiber-reinforced composite material was prepared according to the method of Example 1, except that the plying order of the basalt fiber cloth from top to bottom was: plain cloth 0° / unidirectional cloth -45° / unidirectional cloth 0° / unidirectional cloth +45° / plain cloth 0°.

[0109] Example 3

[0110] A fiber-reinforced composite material was prepared according to the method of Example 1, except that the modified metal oxide in the composite resin was a single modified TiO2 nanoparticle.

[0111] Example 4

[0112] A fiber-reinforced composite material was prepared according to the method of Example 1, except that the plying order of the basalt fiber cloth from top to bottom was: plain cloth 0° / unidirectional cloth 0° / unidirectional cloth 90° / unidirectional cloth 0° / plain cloth 0°; and no modified metal oxide was added to the resin.

[0113] Comparative Example 1

[0114] A fiber-reinforced composite material was prepared according to the method of Example 1, except that the basalt fiber cloth was replaced by glass fiber cloth.

[0115] Comparative Example 2

[0116] A fiber-reinforced composite material was prepared according to the method of Example 2, except that the basalt fiber cloth was replaced by glass fiber cloth.

[0117] Comparative Example 3

[0118] A 3004 aluminum alloy plate with a thickness of 3 mm was used as a comparative example.

[0119] Traffic signs were prepared using the materials of Examples 1 to 4 and Comparative Examples 1 to 3 according to the following method: the materials of Examples 1 to 4 and Comparative Examples 1 to 3 were used as base plates, rivets and aluminum alloy slides were glued on one side of the base plate, and the adhesive was epoxy resin, which was the same resin material as that used to prepare the basalt fiber composite board. The glue-riveting hybrid process was operated in the following steps:

[0120] Use a drilling machine to drill holes in the pre-lapping area. The hole size should be slightly larger than the rivet diameter. Stir the binder evenly and immediately apply it to the pre-lapping area. Then put the rivets in the holes. Use a pressure riveting connection method and hammer the rivet cap with a hammer to rivet the aluminum alloy slide and the sign base plate together. Finally, the sign plate is cured. Place the sign plate in a 60℃ constant temperature box for 1 hour. After curing, take it out and cure it at room temperature for 24 hours. Engrave the words on the reflective film according to the design requirements, then clean the flat surface of the base plate, and paste the reflective film on the other side of the base plate after drying to obtain the traffic sign plate.

[0121] The traffic sign plates obtained in Examples 1 to 4 and Comparative Examples 1 to 3 were tested for relevant performances with reference to national standards GB / T 1447-2005 "Test Method for Tensile Properties of Fiber Reinforced Plastics" and GB / T1449-2005 "Test Method for Bending Properties of Fiber Reinforced Plastics", and the test results are shown in Table 1. Table 1 is a comparison table of tensile strength and bending strength of the traffic sign plates obtained in Examples 1 to 4 and Comparative Examples 1 to 3 at room temperature. The performance of the traffic sign plates obtained in Examples 1 to 4 and Comparative Examples 1 to 3 after being irradiated with ultraviolet light at different temperatures was tested under the following conditions: The test environment conditions refer to GB / T 16422-1997 "Laboratory Light Source Exposure Test Method", the wavelength of the ultraviolet aging test box is 315 to 400 nm, and the selected ultraviolet irradiance is 0.68 W / m 2, relative humidity in the test box is 45% to 55%. Wherein, strength retention rate = (σ1 / σ0) × 100%; σ1 is the tensile strength measured after ultraviolet irradiation, and σ0 is the tensile strength measured at room temperature. Table 2 is a comparison table of tensile strength and strength retention rate of Examples 1 to 4 and Comparative Examples 1 to 3 after ultraviolet irradiation for 1000 hours at different temperatures.

[0122] Table 1 Tensile strength and bending strength of traffic sign plates obtained in Examples 1 to 4 and Comparative Examples 1 to 3

[0123] Example Tensile strength / MPa Bending strength / MPa Example 1 632.51 763.35 Example 2 475.69 674.95 Example 3 553.73 576.22 Example 4 421.11 525.89 Comparative Example 1 301.29 534.88 Comparative Example 2 292.34 324.03 Comparative Example 3 119.64 270.35

[0124] Table 2 Tensile properties of traffic sign plates obtained in Examples 1 to 4 and Comparative Examples 1 to 3 after UV aging

[0125]

[0126] In Table 1, by comparing the results of Examples 1 to 4 with those of Comparative Example 3, it can be seen that the fiber-reinforced composite traffic sign provided by the present invention has higher tensile strength and bending strength than the aluminum alloy traffic sign. The use of fiber-reinforced composite materials fundamentally improves the mechanical properties of the traffic sign, and can withstand greater forces.

[0127] By comparing the basalt fiber composite traffic sign board with the glass fiber composite traffic sign board, in Table 1, by comparing the results obtained in Examples 1 to 4 with those obtained in Comparative Examples 1 to 2, it can be seen that the fiber reinforced composite traffic sign board of the present invention also has higher tensile strength and flexural strength than the glass fiber composite traffic sign board.

[0128] In Table 2, by comparing the results obtained in Example 1 with those obtained in Comparative Example 1, it can be seen that the fiber-reinforced composite traffic sign board of the present invention has a higher tensile strength retention rate under long-term ultraviolet irradiation than the glass fiber composite traffic sign board. And as the temperature increases, the tensile strength retention rate of the basalt fiber composite traffic sign board remains almost unchanged, while the tensile strength retention rate of the glass fiber composite traffic sign board decreases significantly.

[0129] By comparing different plying sequences and nanoparticle addition schemes of basalt fiber composite traffic sign plates, in Table 1, the results obtained in Examples 1 to 4 are compared, and it can be seen that when the plying sequence and the nanoparticle addition scheme are selected as described in Example 1, that is, the plying sequence from top to bottom is: plain cloth 0° / plain cloth -45° / plain cloth 0° / plain cloth +45° / plain cloth 0°, and three modified nanoparticles of CeO2, ZnO and TiO2 are mixed and added to the resin matrix, the total amount of nanoparticles added accounts for 5.0% of the resin mass, and the mass ratio of the three modified nanoparticles is CeO2: ZnO: TiO2 = 2.5: 1.5: 1.0, the tensile strength and bending strength of the sign plate are the largest. When the ply laying sequence and the nanoparticle addition scheme are selected as described in Example 4, that is, the ply laying sequence from top to bottom is: plain cloth 0° / unidirectional cloth 0° / unidirectional cloth 90° / unidirectional cloth 0° / plain cloth 0°, and no nanoparticles are added to the resin matrix, the tensile strength and bending strength of the sign plate are the lowest.

[0130] Comparing the results obtained in Example 1 with those in Example 2, it can be seen that the use of plain weave cloth can greatly improve the mechanical properties of the sign board compared to the use of unidirectional cloth inside the sign board. Plain weave cloth has yarns woven in both the warp and weft directions, so when subjected to load, the fibers in both directions will provide tension, and at the same time, the fiber bundles in both directions will produce mutual friction and mechanical bite force, so that the mechanical properties of the entire layer of fiber cloth are improved. However, the production cost of plain weave cloth is higher than that of unidirectional cloth. Multiple layers of unidirectional cloth with different laying directions can also improve the various directional mechanical properties of composite sign boards, but the mass and thickness will be greater than that of laminates made of plain weave cloth with the same mechanical properties.

[0131] Comparing the results obtained in Example 1 with those obtained in Example 3, it can be seen that the tensile strength of the sign board using the scheme of mixed addition of nanoparticles is increased by 12.5% ​​compared with the tensile strength of the sign board using the scheme of adding only one nanoparticle.

[0132] In the present invention, by modifying the surface of the nanoparticles, new chemical functional groups are added to the surface of the nanoparticles, thereby improving the degree of binding between the nanoparticles and the resin. The modification of the anti-ultraviolet nanoparticles in the resin is enhanced, the anti-ultraviolet aging performance of the matrix itself is greatly improved, and the contact area between the resin matrix and the surface of the basalt fiber is also increased, thereby improving the mechanical properties of the sign board.

[0133] In summary, the basalt fiber composite traffic sign board prepared by the present invention using modified nanoparticle reinforced resin and basalt fiber material with excellent mechanical properties and corrosion resistance has more excellent mechanical properties, anti-ultraviolet aging performance, longer service life, and meets the development goals of green and environmental protection, and has broad development and application prospects.

[0134] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. People can also obtain other embodiments based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.

Claims

1. A fiber-reinforced composite material, characterized in that: comprising a matrix and a reinforcement embedded in the matrix; The reinforcement is a stacked basalt fiber cloth; the basalt fiber cloth on the upper and lower surfaces of the reinforcement is a plain cloth woven from basalt fibers; the angle between the basalt fibers in any two adjacent layers of basalt fiber cloth is 0 to 90°; The matrix is ​​resin.

2. The fiber-reinforced composite material according to claim 1, characterized in that: The basalt fiber cloth except the upper and lower surfaces of the reinforcement body includes one or more of plain cloth, unidirectional cloth and multi-axial cloth woven from basalt fibers.

3. The fiber-reinforced composite material according to claim 1, characterized in that: The resin includes epoxy resin, vinyl resin or unsaturated resin; The resin also includes a modified metal oxide; the modified metal oxide is a metal oxide with a coupling agent grafted on the surface; The mass ratio of the modified metal oxide to the resin in the matrix is ​​0.3 to 6:

100.

4. The fiber-reinforced composite material according to claim 3, characterized in that: The modified metal oxide includes one or more of modified cerium oxide, modified zinc oxide and modified titanium oxide.

5. The fiber-reinforced composite material according to claim 4, characterized in that: The preparation method of the modified cerium oxide comprises the following steps: dissolving a first coupling agent in a first ethanol aqueous solution to obtain a coupling agent solution; first dispersing nano cerium oxide particles in water to obtain a cerium oxide dispersion; The coupling agent solution and the cerium oxide dispersion are first mixed, the pH value is adjusted to 7 to 11, and then a first grafting modification is performed to obtain the modified cerium oxide; The preparation method of the modified zinc oxide comprises the following steps: dispersing the nano zinc oxide particles in a second ethanol aqueous solution to obtain a zinc oxide dispersion; The zinc oxide dispersion and the second coupling agent are mixed for a second time to perform a second grafting modification to obtain the modified zinc oxide; The preparation method of the modified titanium oxide comprises the following steps: dispersing the nano titanium oxide particles in water to obtain a titanium oxide dispersion; The titanium oxide dispersion, the third coupling agent and ethanol are mixed for a third time, the pH value is adjusted to 5-7, and then a third grafting modification is performed to obtain the modified titanium oxide.

6. The method for preparing the fiber-reinforced composite material according to any one of claims 1 to 5, characterized in that: The following steps are involved: mixing the resin and the curing agent to obtain a composite resin; The basalt fiber cloths are stacked to obtain a reinforcement body; the basalt fiber cloths on the upper and lower surfaces of the reinforcement body are both plain cloths woven from basalt fibers; the angle between the basalt fibers in any two adjacent layers of basalt fiber cloth is 0 to 90 degrees; The composite resin and the reinforcement are mixed and molded to obtain the fiber-reinforced composite material.

7. The preparation method according to claim 6, characterized in that: The mass ratio of the curing agent to the resin is 60 to 100:100; The mixing process also adds a modified metal oxide; The molding method includes vacuum infusion molding; The vacuum infusion molding process has a temperature of 150-200° C., a pressure of 3-5 MPa, and a time of 80-120 min.

8. Use of the fiber-reinforced composite material according to any one of claims 1 to 5 or the fiber-reinforced composite material prepared by the preparation method according to claim 6 or 7 in the preparation of road traffic signs.

9. A road traffic sign, characterized in that: It includes a bottom plate, a slide groove arranged on either side of the bottom plate, and a reflective film arranged on the other side of the bottom plate; The base plate is the fiber-reinforced composite material according to any one of claims 1 to 5 or the fiber-reinforced composite material prepared by the preparation method according to claim 6 or 7.

10. The road traffic sign according to claim 9, characterized in that: The slideway is made of aluminum alloy; The connection method between the slideway and the bottom plate includes riveting or glue riveting; the adhesive for glue riveting includes epoxy resin, vinyl resin or unsaturated resin.

Citation Information

Patent Citations

  • High-alkali-salt-corrosion-resistance basalt fiber composite

    CN106589839A

  • Basalt fiber reinforced composite material and preparation method thereof

    CN116278223A

  • High-strength, high-density and high-toughness thermal protection composite material

    CN118752868A

  • Basalt fiber reinforced composite material and manufacturing method thereof

    KR1020150073709A

  • Composite fiber-reinforced resin and impact-absorbing material

    WO2024204015A1